THE OPERATING PRINCIPLE OF THE RADIATOR IS JUSTIFIED THEORETICALLY WITH AI (International journal of artificial intelligence, 2025)
This article analyzes the operating principle of radiators from motor vehicles and its theoretical foundations. thermal processes, radiator production and operation, and heat dissipation mechanisms under various conditions are described. Thermal power through radiators, their scientific fields and technical parameters. based on thermal power, the efficiency of the radiator is highlighted.